DIY: Creating Performance Assessments that Measure Up! - Ann Willemsen-Dunlap; Lisa Barker; Andrew Bland; Trina Croland; John Vozenilek; Gerald Wickham (Association of American Medical Colleges, 2014)
Abstract Introduction The demand for simulation educators to become involved in high stakes performance assessment is growing rapidly. The ability to construct reliable and valid performance assessments, and to evaluate those already available, is necessary in order to ensure clinicians' ability to perform according to set standards, as well as to ensure fair testing practices. Methods This workshop is a 90-minute experiential learning activity designed to improve participants' knowledge, skills, and abilities in creating reliable and valid simulation-based performance assessments and, secondarily, to evaluate assessment instruments that already exist. The files comprising this publication contain didactic material that reviews key concepts related to reliability and validity, construction of performance assessments, and information regarding use of assessment results to improve teaching and learning as well as an activity timeline. Contents also include room set-up information, as well as resource materials and worksheets for participants' use during small-group work. Results This 90-minute workshop was presented for the first time at IMSH 2014, while a modified version of the PowerPoint presentation has been used routinely during Simulation Facilitator Courses since July 2013. It appears that IMSH attendees found this topic of value as all 50 seats were filled 3 weeks prior to the conference date. As further evidence, conference planners raised the attendance cap from the 30, as requested by the authors, to 50. The average score on participant evaluations was 4.1 out of 5. Comments were generally positive. Participants' primary comments pertained to the relatively short timeframe allotted to each phase of group work. Discussion This is an effective and concise resource to help address the increased demand for constructing reliable and valid performance assessments.